Second world record of Metatrichia floripara (Trichiaceae, Myxomycetes), found in Brazil - de Lima, Vitor Xavier; Cavalcanti, Laise De Holanda (Phytotaxa, 2016)
Metatrichia floripara is recorded for the first time in South America, and outside the type locality. A morphological description, illustrations and comments on its distribution are also presented.